HUMAN AND ENVIROMENTAL HARMONY IN THE QUR’AN PERSPECTIVE: ANALYSIS OF ABDULLAH SAEED’S CONTEXTUAL TAFSIR APPROACH. - Siti Zahraini; Bustomi, Yazid Imam (Universitas Islam Indonesia, 2025)
Environmental issues are currently an interesting topic to discuss because of damage such as air pollution, deforestation, and damage to flora and fauna. Humans have a role in exploiting the environment due to a lack of awareness of the harmonious relationship between humans and the environment. Although Islam as a religion of rahmatan lil alaminprovides guidelines on man's relationship with the environment in the Qur'an, this tolerance is beginning to disappear and is increasingly marginalized. In this study, researchers used Abdullah Saeed's contextual interpretation approach to interpret Qur'anic verses that prohibited environmental damage. This prohibition is considered to have instructional value and falls into the category of legal ethics, in Abdullah Saeed's view. The research method used is qualitative with descriptive analysis, with literature studies as a data collection technique. Abdullah Saeed's contextual interpretation approach involves four essential steps. The survey results highlight the relationship between humans and the environment in the Quran, provide new insights to overcome the environmental crisis, and propose solutions based on the Quran’s guidelines to guide humanity.